MICROSTRUCTURAL AND TRANSIENT THERMAL ANALYSIS OF TIG WELDED JOINT SAE 2205 WITH AISI 304 WITH AISI 308 FILLER METAL - Ganesh, C.Selva; Vigraman, T.; Sujith, D.; Velmanikandan, M.; Vetrivel, T. (International Journal of Engineering Technologies and Management Research, 2017)
In the present work SAE 2205 is welded with AISI 304 using AISI 308 filler wire. TIG welding current was maintained at 110, 120 and 130 Amp and the voltage was set at 40 Volt. A constant welding speed of 0.5 mm/s was maintained for all the experiments. The optical microscopic examination of the welded samples revealed the presence of recrystalized zone, mushy zone at the weld metal SAE 2205 side and columnar grains adjacent to the heat affected zone. The maximum hardness value of Rc 29 was observed in the welded region. The increase in hardness value was attributed to absorption of oxygen in the weld metal during welding and solidification of the weld metal. A maximum yield strength of 354 MPa and an ultimate tensile strength value of 549 MPa were obtained for the samples processed at 130 Amp. Combined transient thermal and stress analysis was performed for the dissimilar stainless steel joints made between SAE 2206 and AISI 304L. A maximum Von Mises stress of 85 MPa was obtained for the weld joints made between stainless steel AISI 304 and stainless steel SAE 2205.